Efficacy of Stem Cell Therapy for Tendon Disorders: A Systematic Review. Issue 4 (30th April 2020) - van den Boom, Noortje Anna Clasina; Winters, Marinus; Haisma, Hidde Jacobs; Moen, Maarten Hendrik
Background: Stem cell therapy is an emerging treatment for tendon disorders. Purpose: To systematically review the efficacy of stem cell therapy for patients with tendon disorders. Study Design: Systematic review; Level of evidence, 4. Methods: MEDLINE/PubMed, EMBASE, CINAHL, CENTRAL, PEDro, and SPORTDiscus; trial registers; and gray literature were searched to identify randomized controlled trials (RCTs) and non-RCTs, cohort studies, and case series with 5 or more cases. Studies investigating any type of stem cell therapy for patients with tendon disorders were eligible if they included patient-reported outcome measures or assessed tendon healing. Risk of bias was assessed through use of the Cochrane risk of bias tools. Results: This review included 8 trials (289 patients). All trials had moderate to high risk of bias (level 3 or 4 evidence). In Achilles tendon disorders, 1 trial found that allogenic-derived stem cells led to a faster recovery compared with platelet-rich plasma. Another study found no retears after bone marrow–derived stem cell therapy was used in addition to surgical treatment. There were 4 trials that studied the efficacy of bone marrow–derived stem cell therapy for rotator cuff tears. The controlled trials reported superior patient-reported outcomes and better tendon healing. A further 2 case series found that stem cell therapy improved patient-reported outcomes in patients with patellar tendinopathy and elbow tendinopathy. Conclusion: Level 3 evidence is available to support the efficacy of stem cell therapy for tendon disorders. The findings of available studies are at considerable risk of bias, and evidence-based recommendations for the use of stem cell therapy for tendon disorders in clinical practice cannot be made at this time. Stem cell injections should not be used in clinical practice given the lack of knowledge about potentially serious adverse effects.